INDUSTRI RUMAHAN KUE CANGKIANG DALAM ANALISIS RASIONALITAS TINDAKAN DI KANAGARIAN BATU TABA KABUPATEN AGAM - Sari, Novita; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Kue Cangkiang home industry this is industry Homemaker already down generations in live by society Cangkiang . So that industry this must be on guard and permanent maintained . The increase in fuel makes industry this experience decline, which was originally industry this lived by every House now only stay some House only that remains maintain industry this . Formulation problem in research this that is Why kue Cangkiang home industry this permanent survive . Aim research this for knowing how about it way kue Cangkiang home industry this last and What reason kue Cangkiang home industry this permanent survive . Research this use method research qualitative descriptive , with 5 subjects research . From the results Interview deep and observation in the field , that kue Cangkiang home industry this is industry that is being undertaken society in a manner down generation . After various considerations do industry this more give profit for society compared the work they live it beforehand . With maintain industry this society permanent can conserve tradition that has been scaled back by parents and sufficient needs life . Rationality actions taken society in maintain kue Cangkiang home industry this covers actors , resources , and the norm . And action instrument rationality , action rationality value , and action traditional . Could concluded that kue Cangkiang home industry this last because existence encouragement from parents first for maintain industry this and also is based because awareness self own for maintain industry this. With various consideration industry this more give away advantage in comparison another job. And industry this more have high scores because society not take into account loss what will they get. Industry this also survives with the belief held society for reach destination Keywords: Home Industry kue Cangkiang, Rationality of Action